2008
DOI: 10.1099/jmm.0.47783-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Helicobacter pylori isolates from Chile: occurrence of selective type 1 Lewis b antigen expression in lipopolysaccharide

Abstract: Previous studies have shown that the LPS of Helicobacter pylori isolated from North American and European hosts predominantly expresses type 2 Lewis x (Lex) and Ley epitopes, whilst the LPS from Asian strains has the capacity to express type 1 Lea and Leb structures. The aim of this study was to evaluate the expression of Le antigens and the cytotoxin-associated antigen (CagA) by H. pylori isolates from Chile. A total of 38 isolates were screened. The expression of Le antigens and CagA was determined by whole-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 19 publications
1
22
0
2
Order By: Relevance
“…pylori coloniza la mucosa gástrica de más de la mitad de la población mundial y es responsable de gastritis crónica, úlcera péptica, adenocarcinoma y linfoma asociado a la mucosa gástrica 7,10 . El tratamiento convencional sólo logra entre 70 y 80% de éxito en la cura de los pacientes, por lo que se busca activamente alternativas terapéuticas distintas a los antimicrobianos, como vacunas, probióticos, inactivación fotodinámica, fagoterapia y búsqueda de productos fitoterapéuticos o nutracéuticos [8][9][10][13][14][15][16] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…pylori coloniza la mucosa gástrica de más de la mitad de la población mundial y es responsable de gastritis crónica, úlcera péptica, adenocarcinoma y linfoma asociado a la mucosa gástrica 7,10 . El tratamiento convencional sólo logra entre 70 y 80% de éxito en la cura de los pacientes, por lo que se busca activamente alternativas terapéuticas distintas a los antimicrobianos, como vacunas, probióticos, inactivación fotodinámica, fagoterapia y búsqueda de productos fitoterapéuticos o nutracéuticos [8][9][10][13][14][15][16] .…”
Section: Discussionunclassified
“…Helicobacter pylori es una bacteria que coloniza la mucosa gástrica y se relaciona con gastritis crónica, úlcera gastro-duodenal y cáncer gástrico. La infección por H. pylori constituye una infección crónica extensamente difundida en la especie humana, afectando alrededor de 50% de la población mundial 7,8 . La erradicación de la infección por H. pylori contempla la administración de fármacos inhibidores de la bomba de protones asociado al uso combinado de dos antimicrobianos; los más usados son claritromicina más amoxicilina o metronidazol.…”
unclassified
“…Co-expression of a1,6-glucan with Le x and/or Le y antigens in the majority of H. pylori strains examined suggests the importance of this LPS component in the pathogenesis of H. pylori. We have previously shown that a1,6-glucan affects the colonizing ability of H. pylori and is required for initial colonization of the murine stomach (Altman et al, 2008). In this context, the presence of a1,6-glucan in H. pylori strains isolated from children could be considered another important phenotypic characteristic facilitating successful colonization and contributing to the antigenic diversity of H. pylori LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Following centrifugation (5000 g, 5 min, 4 uC), pellets were suspended in 25 ml PBS to give a final concentration of 10 8 cells ml 21 . WCE was performed as previously described (Altman et al, 2008). Briefly, the wells of a microtitre plate were coated with 100 ml bacterial suspension (10 8 cells ml 21 ) overnight at 4 uC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation